Optimalisasi Media Digital Berbasis Kemaslahatan Umat dalam Program Pahlawan Ekonomi Surabaya - Rio Febriannur Rachman (IQTISHODUNA: Jurnal Ekonomi Islam, 2019)
Abstract This article discusses a number of challenges facing the city of Surabaya as one of the major cities in Indonesia. The city has a number of social problems, including poverty, economic disparity and welfare problems. All that has a correlation with each other, and one of the solutions, is the provision of employment. Since 2010, the City Government of Surabaya has been running the Pahlawan Ekonomi program, which makes Housewives the main target. With hope, they can become the “second economic engine” in the family. Pahlawan Ekonomi provides entrepreneurship training for Housewives, starting from the planning, production, packaging, to marketing. All stages are always under the supervision of a team from the City Government of Surabaya. This paper explores how the implementation of policy in this program, the sustainability, and its correlation to the concept of the Welfare of the People (Kemaslahatan Umat) which is called for in some number of Islamic literatures. In conclusion, this policy has many positive impacts on the community, so that its sustainability can be maintained because it is supported by many parties in Surabaya. The spirit of this program is in harmony with the noble Islamic principles. Moreover, this program has a tagline: Go Global, Go Digital, Go Financial, which makes the program participants ready to compete at the international level. Key Words: Public Policy, the Economy, the Walfare of the People, Digital Abstrak Artikel ini membahas tentang bagaimana sejumlah tantangan yang dihadapi Surabaya sebagai salah satu kota besar di Indonesia. Kota ini memiliki beberapa persoalan sosial, antara lain, kemiskinan, disparitas ekonomi, dan problem kesejahteraan. Semua itu memiliki hubungan satu sama lain, yang salah satu solusi kongkretnya, bisa berupa penyediaan lapangan pekerjaan. Sejak 2010, Pemerintah Kota Surabaya menjalankan program Pahlawan Ekonomi, yang menjadikan para Ibu Rumah Tangga sebagai sasaran utama. Dengan harapan, mereka bisa menjadi mesin ekonomi kedua dalam keluarga. Pahlawan Ekonomi memberikan pelatihan berwirausaha bagi para Ibu Rumah Tangga, mulai dari tahap perencanaan, produksi, pengemasan, hingga pemasaran. Semua tahapan selalu dalam pengawalan tim dari Pemerintah Kota Surabaya. Tulisan ini mengupas tentang bagaimana implementasi kebijakan dalam program ini, keberlanjutannya, dan korelasinya dengan konsep kemaslahatan umat yang diserukan dalam sejumlah literatur keislaman. Kesimpulannya, kebijakan ini memiliki banyak dampak positif di masyarakat, sehingga keberlanjutannya bisa terus terjaga karena didukung oleh banyak pihak di Surabaya. Semangat dari program ini selaras dengan prinsip-prinsip luhur keislaman. Terlebih, program ini memiliki tagline: Go Global, Go Digital, Go Financial, yang menjadikan para peserta program siap bersaing di level internasional. Kata Kunci: Kebijakan Publik, Ekonomi, Kemaslahatan Umat, Digital